An تدخل اللغة الأم في التعبير الكتابي العربي لدى طلاب الفصل الحادي عشر بمدرسة الشيخ عبد الوهاب حسب الله العالية الإسلامية المتوفقة بحر العلوم جومبانج: INTERFERENCE OF MOTHER LANGUAGE TOWARDS ARABIC IN THE WRITING SKILLS OF MAUWH TAMBAKBERAS JOMBANG STUDENTS - Nashoih, Afif Kholisun; Ramadani, Alfiana Fitriyah; Mathoriyah, Lailatul (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
This research aims to determine and describe the forms of language interference that occur among class XI students of Madrasah Aliyah Unggulan K.H. Abd. Wahab Hasbullah and the factors causing Arabic language interference with Indonesian in the ta'bir kitabiy of students at the Unggulan Madrasah Aliyah K.H. Abd. Wahab Hasbulloh. This is because in the process of learning and practicing language, interference becomes a problem that will have a negative impact on the main aspects of language. The emergence of interference is caused by students' lack of understanding of the second language, attachment to the order of the first language and lack of habituation in using the second language. This research is a qualitative descriptive study. Some of the data in this research was obtained from Arabic texts contained in the daily maharah kitabah tests of students at the Unggulan Madrasah Aliyah K.H. Abd. Wahab Hasbulloh class XI in Arabic subjects using the listening method, proficient free-engagement technique and note-taking technique, then analyzed using the intralingual equivalent method to compare elements of Arabic and Indonesian. Based on the results of the analysis, the researcher found several syntactic, semantic and morphological interferences, including, concordance aspect interference, non-adjective noun phrases, inaccurate word selection, errors in Arabic writing and tense aspect interference. In this research, there are two factors that cause language interference, the internal factor is the lack of student motivation in learning Arabic which has an impact on students' lack of understanding of Arabic, lack of habituation in practicing composing Arabic writing and the lack of knowledge possessed by students. External factors: students' habits of using their mother tongue in the surrounding environment.